MGRN1‐mediated ubiquitination of α‐tubulin regulates microtubule dynamics and intracellular transport. (4th October 2017) - Mukherjee, Rukmini; Majumder, Priyanka; Chakrabarti, Oishee
Abstract : MGRN1‐mediated ubiquitination of α ‐tubulin regulates microtubule stability and mitotic spindle positioning in mitotic cells. This study elucidates the effect of MGRN1‐mediated ubiquitination of α ‐tubulin in interphase cells. Here, we show that MGRN1‐mediated ubiquitination regulates dynamics of EB1‐labeled plus ends of microtubules. Intracellular transport of mitochondria and endosomes are affected in cultured cells where functional MGRN1 is depleted. Defects in microtubule‐dependent organellar transport are evident in cells where noncanonical K6‐mediated ubiquitination of α ‐tubulin by MGRN1 is compromised. Loss of MGRN1 has been previously correlated with late‐onset spongiform neurodegeneration. Mislocalised cytosolically exposed PrP ( Ctm PrP) interacts with MGRN1 leading to its loss of function. Expression of Ctm PrP generating mutants of PrP[PrP(A117V) and PrP(KHII)] lead to decrease in MGRN1‐mediated ubiquitination of α ‐tubulin and intracellular transport defects. Brain lysates from PrP(A117V) transgenic mice also indicate loss of tubulin polymerization as compared to non‐transgenic controls. Depletion of MGRN1 activity may hamper physiologically important processes like mitochondrial movement in neuronal processes and intracellular transport of ligands through the endosomal pathway thereby contributing to the pathogenesis of neurodegeneration in certain types of prion diseases. Abstract : Microtubule‐based transport is vital in neurons. Here we show that ubiquitination of α ‐tubulin by MGRN1 regulates microtubule polymer stability and efficiency of cargo transport on microtubule tracks. Functional loss of MGRN1 (by expression of catalytically inactive MGRN1 or presence of cytosolically exposed prion protein, Ctm PrP) drastically compromises intracellular transport of mitochondria and endosomes. Hence, ubiquitination‐mediated microtubule dynamics is important in neurodegeneration associated with certain types of prion diseases.